Leveraging Experiences in Analytics Between Companies Fostering Accelerated Digital Transformation - Surek, Guilherme A. S.; Monteiro, Wellington R.; Coelho, Leandro dos S. (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft), 2021)
Having a competitive advantage puts a company ahead of its competitors and information technology (IT) through analytics has increasingly shown itself to be a competitive advantage. However, achieving full use of this tool is not an easy task and there is no simple recipe that works for all companies, which leads us to seek the exchange of experiences. Knowledge transfer is the key to evolving as a company and promoting an innovation ecosystem. In this article, the authors present two scenarios of large companies, in one of them the company is starting to implement an analytics framework and the other one it has already implemented and has greater maturity in the process of implementation, and then knowledge transfer application is demonstrated.